Peran Pengawasan dalam Meningkatkan Kinerja Karyawan Panen di Sektor Perkebunan - Iskandar, Iskandar; Risman, Risman (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The purpose of this study is to determine the role of supervision in improving the performance of harvest employees in the plantation sector, a case study at PT ABC. To achieve this goal, a study was conducted using a sample of 62 people, using the census method. The data analysis method used simple linear regression. Based on the test results on the supervision variable (X) using SPSS assistance, the t-count was greater than the t-table (5.827> 2,000). Thus, it can be concluded that the X variable or supervision variable has a positive and significant influence on the work productivity of harvest employees in the plantation sector. The value (R2) = (0.601 X 0.601 = 0.361) or 36.1%, so the percentage of contribution or contribution of the supervision variable to the productivity variable is 0.361 or 36.1% while the remaining 63.9% is influenced by other variables that are ignored or not examined in this study. The recommendation that can be submitted is that work supervision of employees must be further improved because from the respondents' answers about work corrections from leaders, they are always constructive rather than blaming, getting the lowest response with an average of 3.26 on the statement quite agree, so it can be said that supervision must be a top priority for employees